Bronchogenic Adenosquamous Cell Carcinoma with Metastasis to Skull: a Case Report - Ghasem Janbabai; Farzad Mokhtari; Ahmad Ramezani; Gholamali Godazande (International Journal of Hematology-Oncology and Stem Cell Research, 2010)
"nIntroduction: Pulmonary Adenosquamous carcinoma is an uncommon histological variety of bronchogenic carcinoma, and has histologic areas differentiated as both squamous cell carcinoma and adenocarcinoma and has clinical behavior more like that of adenocarcinoma. Tumor Stage is higher at the time of diagnosis, and survival is poorer. "nCase presentation: We present a 65 years old woman with bulging in her left frontal site of the head. He also had a dyspnea and abnormal chest X-ray and Histopathological findings for the bronchoscopic biopsy specimen as well revealed bronchogenic adenosquamous carcinoma. Brain MRI with contrast showed a metastasis to skull that resulted in a lytic lesion in frontal bone and leakage of CSF from the skull. "nConclusion: Metastasis of lung cancer to the skull is not a common manifestation of this tumor. However, as we showed, the only manifestation of lung cancer can be the metastatic complications of the tumor.